KEPUASAN KERJA KARYAWAN FOOD AND BEVERAGE SERVICE DEPARTMENT DI TURI BEACH RESORT BATAM - Melliyana Soraya; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This reseach aim to determine employee satisfaction at Turi Beach Resort Batam. Which consists of seven dimensions which are reward, jobitself, promotion opportunity, supervision, co-worker, job condition and job security. The research method used in this research is descriptive quantitative method. The population of this research is all staff of food and beverage service department at Turi Beach Resort Batam. In this study the researchers did not use the sample, because in this study the researchers used all members of the population of 34 people’s. Data collection techniques in this study using questionnaires and interviews. The data analysis technique used is Importance Performance Analysis (IPA) or analysis of the level of importance and performance or employee satisfaction is done by comparing expectations and reality of the responses of respondents. Based on the research conducted, the results of data processing showed a higher expectation rate compared to the reality level, where all the average show the level of satisfaction between reality and expectations of respondents smaller than 100%, with percentage 88.00% then in the interpretation of satisfaction level according to the IPA method is not satisfactory.Keyword: Work satisfaction, employee, F&BService